Crowdlaw and Digital Parliament in Law-Making: Challenges for Chile before the Comparative Experience - Soto Barrientos, Francisco; Fuentes Bravo, Claudio; Millaleo Hernández, Salvador (Revista Chilena de Derecho y Tecnología, 2024)
The present article aims to reflect on relevant experiences of citizen deliberation in processes of open normative creation through digital media that have been carried out in Chile - as forms of digital parliament and in the processes of participation in Chilean constituent processes -, within the context of its growing worldwide development to reconnect citizens with democratic political systems. The developments in Chile, as well as in comparative experience, show the need to regulate adequate deliberation and its impact on the processes of normative creation.